Case report—successful management of acute buried bumper syndrome. Issue 2 (11th February 2022) - Gorji, Leva; Augusta, James; Elrod, Michael
Abstract: Percutaneous gastrostomy (PEG) tube placement is often the preferred approach to addressing nutritional deficits in patients requiring long-term feeding access. Numerous major and minor complications may occur with PEG tube insertion; buried bumper syndrome is a rare, long-term outcome of PEG tube placement, comprising <2.4% of complications. We present the case of a 60-year-old female with laryngeal cancer whom developed acute buried bumper syndrome after PEG tube insertion which was managed successfully with surgical intervention.